+0  
 
0
60
1
avatar

Solve 3a + 4b = 5a - 6b + 24 - 3a for a in terms of b.

 May 11, 2023
 #1
avatar
0

 

Solve 3a + 4b = 5a - 6b + 24 - 3a for a in terms of b.  

 

 

                                                                         3a + 4b = 5a - 6b + 24 - 3a  

 

Put all the a's on one side of the  

equals sign and everything else  

on the other side                                              3a – 5a + 3a  =  –6b – 4b + 24  

 

Total the like terms                                                             a  =  –10b + 24  

.

 May 11, 2023

3 Online Users

avatar
avatar
avatar